Different soluble aggregates of Aβ42 can give rise to cellular toxicity through different mechanisms - Suman De (Nature Portfolio, 2019)
Amyloid beta (Aβ42) peptides form heterogeneous mixtures of aggregates, which are closely linked to Alzheimer’s disease. This study shows how different types of Aβ42 aggregates are associated with distinct mechanisms of toxicity